Immediate, fast, and overcome response of the organism in response to energy osteopathy on the model of primary gonarthrosis (polyparametric and statistical studies) - Yu O Novikov; O G Kantor; JeanPierre Guiliani (Wolters Kluwer Health/LWW, 2019)
In 26 patients with confirmed primary verified gonarthrosis (PGA), a clinical and instrumental examination was conducted to evaluate the response energy osteopathy followed by statistical processing of the data. Three types of the body's response to treatment were identified: immediate, fast, and delayed, which, despite the different informative value of the data of the polyparametric study, allowed judging the effectiveness of the method used.